Polygamy: A Methodological Analysis of Hadith Studies - Ramdani, Acep Dani (Journal of Hadith Studies, 2019)
Polygyny, as a marital system, has a long history that differs across cultures. Before the advent of Islam, polygyny was practiced by various ethnic groups, including the Hebrew and Arab peoples during the Jahiliyah period. In addition, there were also "Salafiyun" ethnic groups, now represented by countries such as Russia, Latvia, the Czech Republic, and Yugoslavia, as well as parts of Germany and England. The practice of polygyny in the Jahiliyah era, or before the time of Prophet Muhammad, was widespread and unrestricted in terms of the number of wives. During the time of Prophet Muhammad, Islam not only allowed monogamous marriages but also permitted polygyny with a maximum limit of four wives. In contrast, those who reject polygyny in Islamic law often argue that it conflicts with gender equality principles or serves as a protest against the practice of free sex. This study aims to explain the concept of polygyny in Islam, its historical evolution from era to era, and the establishment of polygyny during the time of Prophet Muhammad. It also explores the wisdom of Islamic law regarding polygyny and provides a comparison with the Western notion of free sex, which rejects polygyny due to gender equality concerns.